2010
DOI: 10.1073/pnas.1008990107
|View full text |Cite
|
Sign up to set email alerts
|

The RAF inhibitor PLX4032 inhibits ERK signaling and tumor cell proliferation in a V600E BRAF-selective manner

Abstract: Tumors with mutant BRAF and some with mutant RAS are dependent upon ERK signaling for proliferation, and their growth is suppressed by MAPK/ERK kinase (MEK) inhibitors. In contrast, tumor cells with human EGF receptor (HER) kinase activation proliferate in a MEK-independent manner. These findings have led to the development of RAF and MEK inhibitors as anticancer agents. Like MEK inhibitors, the RAF inhibitor PLX4032 inhibits the proliferation of BRAF V600E tumor cells but not that of HER kinase-dependent tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
355
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 422 publications
(382 citation statements)
references
References 36 publications
23
355
1
3
Order By: Relevance
“…The current clinical RAF inhibitors suppress RAF activity selectively in cells expressing BRAF V600E (Halaban et al, 2010;Hatzivassiliou et al, 2010;Heidorn et al, 2010;Joseph et al, 2010;Poulikakos et al, 2010), and they do not inhibit wild-type BRAF because it signals as dimer Yao et al, 2015). This is the basis of the high therapeutic index of these drugs, but RAF dimerization is also predicted to result in drug resistance Samatar and Poulikakos, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current clinical RAF inhibitors suppress RAF activity selectively in cells expressing BRAF V600E (Halaban et al, 2010;Hatzivassiliou et al, 2010;Heidorn et al, 2010;Joseph et al, 2010;Poulikakos et al, 2010), and they do not inhibit wild-type BRAF because it signals as dimer Yao et al, 2015). This is the basis of the high therapeutic index of these drugs, but RAF dimerization is also predicted to result in drug resistance Samatar and Poulikakos, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They bind and inhibit all RAF isoforms in in vitro kinase assays, but they suppress RAF activity and downstream ERK signaling selectively in cells expressing BRAF V600E (Halaban et al, 2010;Hatzivassiliou et al, 2010;Heidorn et al, 2010;Joseph et al, 2010;Poulikakos et al, 2010). In cells with BRAF WT they paradoxically activate RAF and ERK signaling, via a RASdependent mechanism that remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…This insight reveals a previously unidentified point of convergence of MAPK and Akt signaling and may provide a strategy to treat cancers in which MAPK and Akt activities are abnormal. For example, B-Raf-mutated tumors are sensitive to MEK and B-Raf inhibitors, which attenuate cyclin D1 expression and cause G1 arrest (35,36). Inhibition of both MEK and Akt or both B-Raf and Akt may result in more complete and lasting inhibition of Ets-1 target genes, including cyclin D1.…”
Section: Sustained Activation Of Erk1/2 Enhances Cell Survival By Accmentioning
confidence: 99%
“…17,18 It was shown that 3s displayed similar antiproliferative effects against B-Raf V600E mutated cancer cells to that of vemurafenib, whereas compound 3o is moderately more potent (Table 2). In contrast, none of the compounds showed obvious growth inhibition against cell lines expressing B-Raf WT .…”
mentioning
confidence: 99%